2021
DOI: 10.1111/bjh.17470
|View full text |Cite
|
Sign up to set email alerts
|

A universal anti‐Xa assay for rivaroxaban, apixaban, and edoxaban measurements: method validation, diagnostic accuracy and external validation

Abstract: Summary A universal anti‐Xa assay for the determination of rivaroxaban, apixaban and edoxaban drug concentrations would simplify laboratory procedures and facilitate widespread implementation. Following two pilot studies analysing spiked samples and material from 698 patients, we conducted a prospective multicentre cross‐sectional study, including 867 patients treated with rivaroxaban, apixaban or edoxaban in clinical practice to comprehensively evaluate a simple, readily available anti‐Xa assay that would acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Samples were collected regardless of the time of last drug intake, covering the full range of drug levels observed in clinical practice. Ultra-high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) measuring rivaroxaban, apixaban, and edoxaban was used as a reference standard ( 16 , 21 ). The study was approved by the local ethics committees and all hospitals gave local feasibility approval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected regardless of the time of last drug intake, covering the full range of drug levels observed in clinical practice. Ultra-high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) measuring rivaroxaban, apixaban, and edoxaban was used as a reference standard ( 16 , 21 ). The study was approved by the local ethics committees and all hospitals gave local feasibility approval.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, implementing a single-calibration anti-Xa assay for unfractionated heparin, low molecular weight heparin, rivaroxaban, apixaban, and edoxaban would improve laboratory procedures but also the care of patients treated with DOAC. Recently, we demonstrated that a universal, LMWH-calibrated assay can accurately measure DOAC drug levels ( 21 ). However, it remains unclear if this can be achieved using a universal heparin-calibrator intended to detect unfractionated heparin and low molecular weight heparins.…”
Section: Introductionmentioning
confidence: 99%
“…This is a multicenter cross-sectional study conducted between 2018 and 2019 ( 20 ). Patients treated with rivaroxaban, apixaban, or edoxaban in routine clinical practice were included in nine specialized hemostasis laboratories affiliated to tertiary hospitals in Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…Rivaroxaban, apixaban, edoxaban, and edoxaban M4 were quantified by LC-MS/MS as previously described ( 20 ). Briefly, protein precipitation and analyte extraction were performed by adding to the plasma acetonitrile:water 1:1 (v/v), extraction buffer (MassTox TDM Series A, Chromsystems, Gräfelfing, Germany), and precipitation reagent (MassTox TDM Series, Chromsystems, Gräfelfing, Germany) containing the isotope labeled internal standards (13C6 rivaroxaban, 13CD3 apixaban, 13CD2 edoxaban) The samples were vortexed and then centrifuged at 14000 rcf and 20°C for 4 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation